2014
DOI: 10.2174/18715206113136660370
|View full text |Cite
|
Sign up to set email alerts
|

The Immunomodulation and Anti-Inflammatory Effects of Garlic Organosulfur Compounds in Cancer Chemoprevention

Abstract: Garlic (Allium sativum) has been used for centuries as a prophylactic and therapeutic medicinal agent. Importantly, garlic has been suggested to have both cancer-preventive potential as well as significant enhancing effects on the immune system. While these observations are supported experimentally both in vitro and in vivo, the impact of garlic in assisting the immune system in the prevention of cancer still lacks experimental confirmation. Studies addressing the immunomodulatory effects of garlic reveal conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(100 citation statements)
references
References 77 publications
(83 reference statements)
1
95
0
Order By: Relevance
“…Furthermore, recent studies have associated garlic consumption with preventive effects on human cancer (Chiavarini et al, 2016;de Giorgio and Stebbing, 2016;Kaschula et al, 2016;Myneni et al, 2016;Saud et al, 2016;Smith et al, 2016). The hypothesis underlying these studies may partially be explained by the anti-mutagenic and immune-modulatory effects of garlic derived allylsulfur compounds and their ability to exert a direct anti-proliferative effect on growing tumour cells by inducing apoptosis Powolny and Singh, 2008;Schafer and Kaschula, 2014).…”
Section: Bioactivity Perspectives and Applications Of Allium Sulfur mentioning
confidence: 99%
“…Furthermore, recent studies have associated garlic consumption with preventive effects on human cancer (Chiavarini et al, 2016;de Giorgio and Stebbing, 2016;Kaschula et al, 2016;Myneni et al, 2016;Saud et al, 2016;Smith et al, 2016). The hypothesis underlying these studies may partially be explained by the anti-mutagenic and immune-modulatory effects of garlic derived allylsulfur compounds and their ability to exert a direct anti-proliferative effect on growing tumour cells by inducing apoptosis Powolny and Singh, 2008;Schafer and Kaschula, 2014).…”
Section: Bioactivity Perspectives and Applications Of Allium Sulfur mentioning
confidence: 99%
“…Particularly, chronic inflammation creates and maintains a tumor microenvironment where there is migration and a relative abundance of immune inflammatory cells and cytokines [117]. For example, studies have shown that tumor necrosis factor α (TNF-α), IL-8 and IL-10 levels are higher in patients with inflammationassociated cancer [118]. DADS has been shown to have both immunomodulatory and anti-inflammatory effects in several types of cancer [7,119].…”
Section: The Inhibition Of Inflammation By Dadsmentioning
confidence: 99%
“…Allium sativum has significant enhancing effects on the immune system (Schäfer and Kaschula 2014). It has an ability to increase nitric oxide synthase activity intracellularly which explains why many of the therapeutic actions of garlic parallel the physiological effects of nitric oxide (Morihara et al 2002).…”
Section: Discussionmentioning
confidence: 99%